High-entropy base material nano coating cutting tool and preparation method thereof
A high entropy substrate nano-coating tool with a TiAlN base and TiSiN top coating, combined with surface activation, addresses the challenges of titanium alloy machining by improving bonding strength and stability, enhancing tool performance and longevity.
Patent Information
- Application Number
- CN202411312685.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Titanium alloys are difficult to machine due to their unique material properties, leading to rapid wear and premature failure of machining tools, particularly from diffusion wear, which affects machining quality and increases costs.
A high entropy substrate nano-coating tool is prepared by forming a TiAlN base coating and a TiSiN top coating on a metal ceramic substrate, with a surface activation treatment using alkali and acid solutions followed by K2Cr2O7 activation, to enhance bonding strength and stability.
The multi-layer coating significantly improves the high-temperature oxidation resistance and structural stability of the tool, maintaining firm connections and inhibiting crack initiation, thereby enhancing tool performance and extending its lifespan.
Smart Images

Figure CN119194351A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of metallurgical technology and more specifically relates to a high entropy substrate nano-coated tool and a preparation method thereof. Background Art
[0002] Titanium alloys have many excellent material properties, such as high mechanical properties and corrosion resistance, biosafety and good reactivity with biological tissues, and are widely used in research and development and production. For example: 1. Aerospace: titanium alloys are used to manufacture mechanical equipment such as aircraft engines and aerodynamic systems, or to make important parts such as engine casings and blades; 2. Biomedical: titanium alloys are used to make or repair artificial implants in the human body, such as artificial bones; 3. Military and shipbuilding: titanium alloys are used to make engine tanks, armored vehicles, and structural parts of large ships; Daily life: titanium alloys are used to make high-strength parts such as bearings and bicycle frames.
[0003] Despite the wide range of applications for titanium alloys, their processing and manufacturing methods are a challenge. Although direct forming methods such as precision forging have been developed to minimize the processing of titanium parts, many parts, such as those for gas turbine engines and fuselages, are still manufactured through operations such as turning, drilling and milling to keep costs low. However, titanium alloys are also difficult to machine because of their unique material properties: the low thermal conductivity of titanium alloys, the high cutting temperatures and high strengths produced by them lead to severe abrasive wear and diffusion wear of the tool; the low modulus of titanium alloys leads to chatter and high radial cutting forces; and the high chemical reactivity of titanium alloys promotes the further progress of diffusion wear. Therefore, the common wear of tools during titanium alloy machining is mainly the combined effect of mechanical wear, plastic deformation, workpiece material adhesion and diffusion wear between the workpiece and the tool, and the diffusion wear between the tool and the workpiece plays a more critical role at high cutting speeds. When higher cutting speeds are applied to titanium alloys, the relative contribution of tool diffusion wear to total wear increases exponentially. These unique material properties of titanium alloys lead to rapid wear and premature failure of machining tools, seriously affecting the machining quality of titanium alloy workpieces and greatly increasing the machining cost of titanium alloys. Summary of the invention
[0004] The technical problem to be solved by the present invention is that a high entropy substrate nano-coating formed by thermal spraying on the surface of a tool may fall off during long-term use of the product and have insufficient bonding strength with the tool substrate. The present invention provides a high entropy substrate nano-coating tool and a preparation method thereof.
[0005] The purpose of the invention is to provide a high entropy substrate nano-coated tool.
[0006] Another object of the present invention is to provide a method for preparing a high entropy substrate nano-coated tool.
[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0008] A method for preparing a high entropy substrate nano-coated tool, the specific preparation steps comprising:
[0009] Preparation of metal ceramics:
[0010] The ingredients are prepared according to the following weight parts to obtain C1 material: Ti: 15-52 parts; Ni: 5.0-15.0 parts; Co: 5.0-15.0 parts; Cr: 5.0-15.0 parts; Nb: 5.0-15.0 parts; Ta: 5.0-15.0 parts; Mo: 2.0-16.0 parts; W: 2.0-15.0 parts; C: 2.0-7.0 parts; N: 2.0-3.0 parts;
[0011] The ingredients are prepared according to the following weight parts to obtain C2 material: Ti: 50-62 parts; Ni: 2.0-3.0 parts; Co: 2.0-3.0 parts; Cr: 2.0-3.0 parts; Nb: 2.0-3.0 parts; Ta: 2.0-3.0 parts; Mo: 11.0-16.0 parts; W: 7.0-15.0 parts; C: 7.0-11.0 parts; N: 2.0-3.0 parts;
[0012] The C1 material and the C2 material are respectively ball-milled and mixed with a molding agent to obtain a C1 ball-milled material and a C2 ball-milled material respectively;
[0013] Prepare C1 ball abrasive and C2 ball abrasive in a mass ratio of 1:4;
[0014] First, the C2 abrasive is loaded into the mold and pre-pressed; then the C1 abrasive is laid on the surface of the pre-pressed C2 abrasive, and after pre-pressing, the final pressing is performed;
[0015] After the final pressing, the material is subjected to microwave vacuum sintering at a temperature of 1400-1500°C and a vacuum degree of no more than 0.1 Pa, and then cooled and discharged to obtain a metal ceramic.
[0016] Coating treatment:
[0017] A TiAlN base coating is first deposited on the surface of the metal ceramic, and then a TiSiN top coating is deposited on the surface of the base coating to obtain a high entropy substrate nano-coated tool.
[0018] Furthermore, the specific preparation steps also include:
[0019] Before the coating treatment, the metal ceramic is subjected to surface activation treatment;
[0020] The surface activation treatment comprises:
[0021] After grinding and polishing, the metal ceramic is washed with alkali and acid in sequence, and then activated with K2Cr2O7 solution for 1-3 hours.
[0022] Further, the alkali washing comprises:
[0023] The surface of the metal ceramic is cleaned with a sodium hydroxide solution having a concentration of 1-3 mol / L for 20-90 seconds.
[0024] Further, the pickling comprises:
[0025] The alkali-washed metal ceramic surface is cleaned for 45-100 seconds using a strong acid solution with a concentration of 1.2-3.5 mol / L.
[0026] Furthermore, the strong acid solution is prepared by compounding a nitric acid solution with a mass fraction of 10%, a hydrochloric acid solution with a mass fraction of 10%, and a hydrofluoric acid solution with a mass fraction of 10% in a mass ratio of 1:1:2.
[0027] Furthermore, the coating treatment further comprises:
[0028] Transfer the metal ceramic into the coating furnace and evacuate to a vacuum degree of 3×10 -3 Pa, the furnace temperature is set to 350-550℃, the sample speed is set to 2-5r / min, in a nitrogen atmosphere, Ti40Al60 target is used as the target material, the negative bias voltage is from -20V to 200V, the target current is gradually increased to 120A-160A, the frequency is 30kHz, the duty cycle is 75%, the nitrogen flow rate is 20-120sccm, and the deposition time is 30min. Then, Ti85Si15 target is used as the target material, and the deposition is continued for 30min. Then, the furnace is cooled to room temperature and the material is discharged to complete the coating treatment.
[0029] Further, the pre-pressing comprises: pressing for 3-5 minutes at a pressure of 10-12T;
[0030] The final pressing molding comprises: pressing for 8-10 minutes at a pressure of 100-110T.
[0031] A high entropy substrate nano-coated cutting tool is prepared by the above-mentioned preparation method.
[0032] Beneficial technical effects:
[0033] (1) The matrix prepared by the formula system designed by the present invention is a high-entropy metal ceramic, which can give full play to the high-entropy effect of high-entropy materials and significantly improve the high-temperature oxidation resistance and high-temperature structural stability of the coated tool; in particular, the present invention forms a multi-layer coating by sequential deposition. Specifically, TiAlN is first deposited on the surface of the metal ceramic as a base coating, and then TiSiN is deposited on its surface as a top coating. Such a design can utilize the closer lattice parameter characteristics between TiAlN and the metal ceramic substrate of the present invention, so that it is easier to be captured by the vacancies on the surface of the metal ceramic substrate, thereby achieving a firm connection between the base coating and the metal ceramic substrate. On this basis, TiSiN can effectively inhibit the initiation and expansion of cracks in the coating due to its higher toughness and good interface bonding with the base coating, thereby improving the stability of the coating itself under high temperature conditions, and ultimately improving the overall performance of the tool;
[0034] (2) In addition, before depositing the coating on the surface of the metal ceramic substrate, an activation treatment is first performed. Specifically, after physical grinding and polishing, it is continued to be treated with alkali solution and acid solution, and then activated with K2Cr2O7 solution. In this way, the high entropy metal phase on the surface of the metal ceramic can be treated with bond breaking and atom deficiency, so that in the surface high entropy alloy layer, a large area of metal atomic vacancies appear in the high entropy alloy phase with severe lattice distortion, thereby further increasing its ability to capture atoms, making the bonding force between the metal ceramic substrate and the coating more firm and reliable. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is the overall morphology of the coating cross section of Example 1 of the present invention;
[0036] Figure 2 This is the dark field image of the columnar structure inside the coating of Example 1 of the present invention. DETAILED DESCRIPTION
[0037] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0038] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0039] Example 1
[0040] Preparation of metal ceramics:
[0041] The ingredients are prepared according to the following weight parts to obtain C1 material: Ti: 15 parts; Ni: 5.0 parts; Co: 5.0 parts; Cr: 5.0 parts; Nb: 5.0 parts; Ta: 5.0 parts; Mo: 2.0 parts; W: 2.0 parts; C: 2.0 parts; N: 2.0 parts;
[0042] The ingredients are prepared according to the following weight parts to obtain C2 material: Ti: 50 parts; Ni: 2.0 parts; Co: 2.0 parts; Cr: 2.0 parts; Nb: 2.0 parts; Ta: 2.0 parts; Mo: 11.0 parts; W: 7.0 parts; C: 7.0 parts; N: 2.0 parts;
[0043] The C1 material and the C2 material are respectively ball-milled and mixed with a molding agent to obtain a C1 ball-milled material and a C2 ball-milled material respectively;
[0044] Prepare C1 ball abrasive and C2 ball abrasive in a mass ratio of 1:4;
[0045] First, the C2 ball mill is loaded into the mold, and then pre-pressed for 3 minutes at a pressure of 10T; then the C1 ball mill is laid on the surface of the pre-pressed C2 ball mill, and pre-pressed for 3 minutes at a pressure of 10T, and finally pressed for 8 minutes at a pressure of 100T to form;
[0046] After the final pressing, the material is subjected to microwave vacuum sintering for 1 hour at a temperature of 1400°C and a vacuum degree of no more than 0.1 Pa, and then cooled and discharged to obtain a metal ceramic.
[0047] Surface activation treatment:
[0048] After grinding and polishing, the metal ceramics were washed with alkali and acid in turn, and then activated with K2Cr2O7 solution for 1 h, and then washed with anhydrous ethanol three times;
[0049] The alkali washing comprises:
[0050] The metal ceramic surface was cleaned with a 1 mol / L sodium hydroxide solution for 20 seconds.
[0051] The pickling comprises:
[0052] The alkali-washed metal ceramic surface was cleaned for 45 seconds using a strong acid solution with a concentration of 1.2 mol / L;
[0053] The strong acid solution is prepared by mixing 10% nitric acid solution, 10% hydrochloric acid solution and 10% hydrofluoric acid solution in a mass ratio of 1:1:2.
[0054] Coating treatment:
[0055] Transfer the metal ceramic into the coating furnace and evacuate to a vacuum degree of 3×10 -3 Pa, the furnace temperature was set to 350 ° C, the sample speed was set to 2r / min, in a nitrogen atmosphere, Ti40Al60 target was used as the target material, the negative bias voltage was gradually increased from -20V, the target current was 120A, the frequency was 30kHz, the duty cycle was 75%, the nitrogen flow rate was 20sccm, the deposition time was 30min, after the TiAlN bottom coating was deposited, Ti85Si15 target was used as the target material, and the deposition continued for 30min, after the TiSiN top coating was deposited, the furnace was cooled to room temperature, and the material was discharged, the coating treatment was completed, and a high entropy substrate nano-coated tool was obtained.
[0056] Example 2
[0057] Preparation of metal ceramics:
[0058] The ingredients are prepared according to the following weight parts to obtain C1 material: Ti: 32 parts; Ni: 8.5 parts; Co: 7.0 parts; Cr: 9.2 parts; Nb: 9.1.0 parts; Ta: 8.0 parts; Mo: 6.0 parts; W: 7.0 parts; C: 5.0 parts; N: 2.5 parts;
[0059] The ingredients are prepared according to the following weight parts to obtain C2 material: Ti: 58 parts; Ni: 2.6 parts; Co: 2.4 parts; Cr: 2.5 parts; Nb: 2.3 parts; Ta: 2.5 parts; Mo: 13.0 parts; W: 10.0 parts; C: 9.0 parts; N: 2.5 parts;
[0060] The C1 material and the C2 material are respectively ball-milled and mixed with a molding agent to obtain a C1 ball-milled material and a C2 ball-milled material respectively;
[0061] Prepare C1 ball abrasive and C2 ball abrasive in a mass ratio of 1:4;
[0062] First, the C2 ball mill is loaded into the mold, and then pre-pressed for 4 minutes at a pressure of 11T; then the C1 ball mill is laid on the surface of the pre-pressed C2 ball mill, and pre-pressed for 4 minutes at a pressure of 11T, and finally pressed for 9 minutes at a pressure of 105T to form;
[0063] After the final pressing, the material is subjected to microwave vacuum sintering at a temperature of 1450°C and a vacuum degree of no more than 0.1 Pa, and then cooled and discharged to obtain a metal ceramic.
[0064] Surface activation treatment:
[0065] After grinding and polishing, the metal ceramics were washed with alkali and acid in turn, and then activated with K2Cr2O7 solution for 2 h, and then washed with anhydrous ethanol three times;
[0066] The alkali washing comprises:
[0067] The metal ceramic surface was cleaned with a 2 mol / L sodium hydroxide solution for 60 seconds.
[0068] The pickling comprises:
[0069] The alkali-washed metal ceramic surface was cleaned with a strong acid solution of 2.5 mol / L for 80 seconds;
[0070] The strong acid solution is prepared by mixing 10% nitric acid solution, 10% hydrochloric acid solution and 10% hydrofluoric acid solution in a mass ratio of 1:1:2.
[0071] Coating treatment:
[0072] Transfer the metal ceramic into the coating furnace and evacuate to a vacuum degree of 3×10 -3 Pa, the furnace temperature was set to 450 ° C, the sample speed was set to 3r / min, in a nitrogen atmosphere, Ti40Al60 target was used as the target material, the negative bias voltage was gradually increased from -120V, the target current was 140A, the frequency was 30kHz, the duty cycle was 75%, the nitrogen flow rate was 70sccm, the deposition time was 30min, after the TiAlN bottom coating was deposited, Ti85Si15 target was used as the target material, and the deposition continued for 30min, after the TiSiN top coating was deposited, the furnace was cooled to room temperature, and the material was discharged, the coating treatment was completed, and the high entropy substrate nano-coated tool was obtained.
[0073] Example 3
[0074] Preparation of metal ceramics:
[0075] The ingredients are prepared according to the following weight parts to obtain C1 material: Ti: 52 parts; Ni: 15.0 parts; Co: 15.0 parts; Cr: 15.0 parts; Nb: 15.0 parts; Ta: 15.0 parts; Mo: 16.0 parts; W: 15.0 parts; C: 7.0 parts; N: 3.0 parts;
[0076] The ingredients are prepared according to the following weight parts to obtain C2 material: Ti: 62 parts; Ni: 3.0 parts; Co: 3.0 parts; Cr: 3.0 parts; Nb: 3.0 parts; Ta: 3.0 parts; Mo: 16.0 parts; W: 15.0 parts; C: 11.0 parts; N: 3.0 parts;
[0077] The C1 material and the C2 material are respectively ball-milled and mixed with a molding agent to obtain a C1 ball-milled material and a C2 ball-milled material respectively;
[0078] Prepare C1 ball abrasive and C2 ball abrasive in a mass ratio of 1:4;
[0079] First, the C2 ball mill is loaded into the mold, and pre-pressed for 5 minutes at a pressure of 12T; then the C1 ball mill is laid on the surface of the pre-pressed C2 ball mill, and pre-pressed for 5 minutes at a pressure of 12T, and finally pressed for 10 minutes at a pressure of 110T to form;
[0080] After the final pressing, the material is subjected to microwave vacuum sintering at a temperature of 1500°C and a vacuum degree of no more than 0.1 Pa, and then cooled and discharged to obtain a metal ceramic.
[0081] Surface activation treatment:
[0082] After grinding and polishing, the metal ceramics were washed with alkali and acid in turn, and then activated with K2Cr2O7 solution for 3 h, and then washed with anhydrous ethanol three times;
[0083] The alkali washing comprises:
[0084] The metal ceramic surface was cleaned with a 3 mol / L sodium hydroxide solution for 90 seconds.
[0085] The pickling comprises:
[0086] The alkali-washed metal ceramic surface was cleaned with a strong acid solution with a concentration of 3.5 mol / L for 100 s;
[0087] The strong acid solution is prepared by mixing 10% nitric acid solution, 10% hydrochloric acid solution and 10% hydrofluoric acid solution in a mass ratio of 1:1:2.
[0088] Coating treatment:
[0089] Transfer the metal ceramic into the coating furnace and evacuate to a vacuum degree of 3×10 -3 Pa, the furnace temperature is set to 550℃, the sample speed is set to 5r / min, in a nitrogen atmosphere, a Ti40Al60 target is used as the target material, the negative bias voltage is gradually increased from -200V, the target current is 160A, the frequency is 30kHz, the duty cycle is 75%, the nitrogen flow rate is 120sccm, the deposition time is 30min, after the TiAlN bottom coating is deposited, a Ti85Si15 target is used as the target material, and the deposition is continued for 30min, after the TiSiN top coating is deposited, the furnace is cooled to room temperature, and the material is discharged, the coating treatment is completed, and a high entropy substrate nano-coated tool is obtained.
[0090] Example 4
[0091] The present embodiment differs from the embodiment 1 in that an equal mass of anhydrous ethanol is used to replace the K2Cr2O7 solution, and the other conditions remain unchanged.
[0092] Example 5
[0093] The present embodiment is different from the embodiment 1 in that water washing is used instead of alkali washing and acid washing, and the other conditions remain unchanged.
[0094] Comparative Example 1
[0095] The difference between this comparative example and Example 1 is that no TiSiN top coating is deposited, and other conditions remain unchanged.
[0096] Comparative Example 2
[0097] The difference between this comparative example and Example 1 is that no TiAlN undercoat layer is deposited, and other conditions remain unchanged.
[0098] The performance tests were performed on the products obtained in the above examples and comparative examples. The specific test methods and test results are as follows:
[0099] Prepare samples: Make sure the coating surface is clean and free of oil and dirt, and the coating should be uniform without obvious defects;
[0100] Select scratch tool: Use a stylus with a smooth conical tip (diamond indenter) for testing;
[0101] Set up the scratch tester: Adjust the scratch tester and set the scratch speed and loading rate. The scratch speed is set at 6mm / min.
[0102] Perform scratch test: First, use a scratch tester at room temperature to gradually increase the load on the scratching needle, and move the sample at the same time, so that the scratching needle scratches the coating surface;
[0103] After heating the sample to 600°C, the scratch tester was used again in a nitrogen atmosphere to gradually increase the load on the scratching needle while moving the sample so that the scratching needle scratched the coating surface.
[0104] Monitoring the scratching process: The scratching process is monitored by acoustic emission detection technology or tangential force detection technology. When the coating is damaged, an acoustic signal is emitted or the tangential force changes.
[0105] Record critical load: The load applied when the coating fails is called critical load, which is a measure of the adhesion strength between the coating and the substrate. The detailed test results are shown in Table 1;
[0106] Table 1: Product performance test results
[0107] Critical load at room temperature / N 600℃ critical load / N Example 1 93.4 92.9 Example 2 94.0 93.2 Example 3 93.7 93.0 Example 4 88.1 86.6 Example 5 89.2 87.4 Comparative Example 1 76.1 70.2 Comparative Example 2 74.8 68.1
[0108] It can be seen from the test results in Table 1 that the coating of the product obtained by the present invention has high adhesion and can maintain stable performance under a large load. In addition, the product performance can be effectively maintained as the temperature increases.
[0109] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a high entropy substrate nano-coated tool, characterized in that: The specific preparation steps include: Preparation of metal ceramics: The ingredients are prepared according to the following weight parts to obtain C1 material: Ti: 15-52 parts; Ni: 5.0-15.0 parts; Co: 5.0-15.0 parts; Cr: 5.0-15.0 parts; Nb: 5.0-15.0 parts; Ta: 5.0-15.0 parts; Mo: 2.0-16.0 parts; W: 2.0-15.0 parts; C: 2.0-7.0 parts; N: 2.0-3.0 parts; The ingredients are prepared according to the following weight parts to obtain C2 material: Ti: 50-62 parts; Ni: 2.0-3.0 parts; Co: 2.0-3.0 parts; Cr: 2.0-3.0 parts; Nb: 2.0-3.0 parts; Ta: 2.0-3.0 parts; Mo: 11.0-16.0 parts; W: 7.0-15.0 parts; C: 7.0-11.0 parts; N: 2.0-3.0 parts; The C1 material and the C2 material are respectively ball-milled and mixed with a molding agent to obtain a C1 ball-milled material and a C2 ball-milled material respectively; Prepare C1 ball abrasive and C2 ball abrasive in a mass ratio of 1:4; First, the C2 abrasive is loaded into the mold and pre-pressed; then the C1 abrasive is laid on the surface of the pre-pressed C2 abrasive, and after pre-pressing, the final pressing is performed; After the final pressing, the material is subjected to microwave vacuum sintering at a temperature of 1400-1500°C and a vacuum degree of no more than 0.1 Pa, and then cooled and discharged to obtain a metal ceramic. Coating treatment: A TiAlN base coating is first deposited on the surface of the metal ceramic, and then a TiSiN top coating is deposited on the surface of the base coating to obtain a high entropy substrate nano-coated tool.
2. The method for preparing a high entropy substrate nano-coated tool according to claim 1, characterized in that: The specific preparation steps also include: Before the coating treatment, the metal ceramic is subjected to surface activation treatment; The surface activation treatment comprises: After grinding and polishing, the metal ceramic is washed with alkali and acid in sequence, and then activated with K2Cr2O7 solution for 1-3 hours.
3. The method for preparing a high entropy substrate nano-coated tool according to claim 2, characterized in that: The alkali washing comprises: The surface of the metal ceramic is cleaned with a sodium hydroxide solution having a concentration of 1-3 mol / L for 20-90 seconds.
4. The method for preparing a high entropy substrate nano-coated tool according to claim 2, characterized in that: The pickling comprises: The alkali-washed metal ceramic surface is cleaned for 45-100 seconds using a strong acid solution with a concentration of 1.2-3.5 mol / L.
5. The method for preparing a high entropy substrate nano-coated tool according to claim 4, characterized in that: The strong acid solution is prepared by compounding a nitric acid solution with a mass fraction of 10%, a hydrochloric acid solution with a mass fraction of 10%, and a hydrofluoric acid solution with a mass fraction of 10% in a mass ratio of 1:1:
2.
6. The method for preparing a high entropy substrate nano-coated tool according to claim 1, characterized in that: The coating process also includes: Transfer the metal ceramic into the coating furnace and evacuate to a vacuum degree of 3×10 -3 Pa, the furnace temperature is set to 350-550℃, the sample speed is set to 2-5r / min, in a nitrogen atmosphere, Ti40Al60 target is used as the target material, the negative bias voltage is from -20V to 200V, the target current is gradually increased to 120A-160A, the frequency is 30kHz, the duty cycle is 75%, the nitrogen flow rate is 20-120sccm, and the deposition time is 30min. Then, Ti85Si15 target is used as the target material, and the deposition is continued for 30min. Then, the furnace is cooled to room temperature and the material is discharged to complete the coating treatment.
7. The method for preparing a high entropy substrate nano-coated tool according to claim 1, characterized in that: The pre-pressing comprises: pressing for 3-5 minutes at a pressure of 10-12T; The final pressing molding comprises: pressing for 8-10 minutes at a pressure of 100-110T.
8. A high entropy substrate nano-coated tool, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation method for graphene modified Cu-Zn composite coating on surface of titanium alloy
CN110592625A
Transition metal carbonitride-based high-entropy metal ceramic and preparation method and application thereof
CN110607473A
Method for improving hardness, film / substrate binding force and friction performance of coating
CN115961257A
Preparation method of high-entropy metal ceramic with coreless structure
CN118621171A
Metal-ceramic cutting tool material and its preparation method
CN1410574A
